Noninvasive Technique for the Diagnosis of Patent Ductus Arteriosus in Premature Infants by Analyzing Pulse Wave Phases on Photoplethysmography Signals Measured in the Right Hand and the Left Foot - Goudjil, Sabrina (Public Library of Science, 2014)
OBJECTIVE: To evaluate the impact of patent ductus arteriosus (PDA) on the pulse phase difference (PPD) between the left foot (postductal region) and the right hand (preductal region). MATERIALS AND METHODS: PPD was determined from arterial photoplethysmography signals (pulse waves) measured by infrared sensors routinely used for pulse oximetry in 56 premature infants less than 32 weeks gestation. Only infants with significant PDA (sPDA) diagnosed by echocardiography were treated with ibuprofen (for 3 days). Patients were classified according to whether or not they responded (Success/Failure) to this treatment. The Control group was composed of infants in whom ductus had already closed spontaneously at the time of the first echocardiography. The 3 groups were compared in terms of PPD at the beginning (T1) and at the end (T2) of the study. For patients in the Failure (n = 17) and Success groups (n = 18), T1 corresponded to the first day of treatment and T2 to the day after completion of the course of ibuprofen. In the Control group (n = 21), T1 corresponded to 1 to 3 days of life (DOL), and T2 to 4–6 DOL. RESULTS: Compared to the Control group, PPD was higher in the Failure (at T1 and T2) and Success (at T1) groups characterized by sPDA. After ibuprofen therapy, PPD in the Success group decreased to about the level observed in the Control group. The area under the ROC curve of PPD for the diagnosis of sPDA was 0.98 (95% CI 0.96–1); for an optimal cut-off of PPD ≥1.65 deg/cm, the sensitivity was 94.2% and the specificity was 98.3%. CONCLUSION: In this study, PPD was correlated with ductus arteriosus status evaluated by echocardiography, indicating involvement of the ductal shunt in the mechanism of redistribution in systemic vascular territories. PPD can be considered for the diagnosis of hemodynamically significant PDA.